(untitled) (Bangladesh Journal of Plant Taxonomy, 2011)
Duchesnea brunneus J. Z. Dong (Solanaceae) is described and illustrated here as a new species from Hubei, China. The newly described species is compared with its closely related species. Key words: Duchesnea brunneus; Rosaceae; New species; China. DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9302 Bangladesh J. Plant Taxon. 18(2): 159-162, 2011 (December)